2000
DOI: 10.1083/jcb.148.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Expression of N-Cadherin in Breast Cancer Cells Induces Cell Migration, Invasion, and Metastasis

Abstract: E- and N-cadherin are calcium-dependent cell adhesion molecules that mediate cell–cell adhesion and also modulate cell migration and tumor invasiveness. The loss of E-cadherin–mediated adhesion has been shown to play an important role in the transition of epithelial tumors from a benign to an invasive state. However, recent evidence indicates that another member of the cadherin family, N-cadherin, is expressed in highly invasive tumor cell lines that lacked E-cadherin expression. These findings have raised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
669
12
14

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 827 publications
(745 citation statements)
references
References 51 publications
(78 reference statements)
50
669
12
14
Order By: Relevance
“…It has been suggested that increased expression of mesenchymal cadherins such as N-cadherin and cadherin 11 increases the motility and invasiveness of epithelial cells (Hazan et al, 2000;Feltes et al, 2002). Here, TMPRRS4-overexpressing SW480 cells displayed membrane ruffling and lamellipodia formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased expression of mesenchymal cadherins such as N-cadherin and cadherin 11 increases the motility and invasiveness of epithelial cells (Hazan et al, 2000;Feltes et al, 2002). Here, TMPRRS4-overexpressing SW480 cells displayed membrane ruffling and lamellipodia formation.…”
Section: Discussionmentioning
confidence: 99%
“…N-Cadherin is expressed in migratory cells which are undergoing EMT, and has been shown to increase cell motility even in the presence of E-Cadherin (Hazan et al, 2000;Nieman et al, 1999). During EMT the expression of Ecadherin defervesces and the expression of N-cadherin increases (Nakajima et al, 2004).…”
Section: Snail2 Expression Is Associated With a Change From E-cadherimentioning
confidence: 99%
“…39 Further, exogenous expression of N-cadherin in breast cancer cells enhances motile, invasive and metastatic ability. 40 Human squamous carcinoma cells that express N-cadherin along with a decreased expression of E-and P-cadherin disrupt cell-cell adhesion and induce a scattered fibroblastic phenotype. 41 Taken together, the loss of E-cadherin and induction of N-cadherin by HOXD3-overexpression are likely to contribute to the invasive and metastatic phenotype.…”
Section: Matrix-degradative Property Of the Hoxd3 Transfectantmentioning
confidence: 99%